Increased sensitivity of SARS-CoV-2 to type III interferon in human intestinal epithelial cells - Metz Zumarán, Camila; Kee, Carmon; Doldan, Patricio; Guo, Cuncai; Stanifer, Megan; Boulant, Steeve (Journal of virology, 2022)
The coronavirus SARS-CoV-2 caused the COVID-19 global pandemic leading to 5.3 million deaths worldwide as of December 2021. The human intestine was found to be a major viral target which could have a strong impact on virus spread and pathogenesis since it is one of the largest organs. While type I interferons (IFNs) are key cytokines acting against systemic virus spread, in the human intestine type III IFNs play a major role by restricting virus infection and dissemination without disturbing homeostasis. Recent studies showed that both type I and III IFNs can inhibit SARS-CoV-2 infection, but it is not clear whether one IFN controls SARS-CoV-2 infection of the human intestine better or with a faster kinetics. In this study, we could show that type I and III IFNs both possess antiviral activity against SARS-CoV-2 in human intestinal epithelial cells (hIECs); however, type III IFN is more potent. Shorter type III IFN pretreatment times and lower concentrations were required to efficiently reduce virus load compared to type I IFNs. Moreover, type III IFNs significantly inhibited SARS-CoV-2 even 4 h postinfection and induced a long-lasting antiviral effect in hIECs. Importantly, the sensitivity of SARS-CoV-2 to type III IFNs was virus specific since type III IFN did not control VSV infection as efficiently. Together, these results suggest that type III IFNs have a higher potential for IFN-based treatment of SARS-CoV-2 intestinal infection compared to type I IFNs., IMPORTANCE SARS-CoV-2 infection is not restricted to the respiratory tract and a large number of COVID-19 patients experience gastrointestinal distress. Interferons are key molecules produced by the cell to combat virus infection. Here, we evaluated how two types of interferons (type I and III) can combat SARS-CoV-2 infection of human gut cells. We found that type III interferons were crucial to control SARS-CoV-2 infection when added both before and after infection. Importantly, type III interferons were also able to produce a long-lasting effect, as cells were protected from SARS-CoV-2 infection up to 72 h posttreatment. This study suggested an alternative treatment possibility for SARS-CoV-2 infection.